Determinants of cash waqf giving behavior intention in Malaysia : a study of donors in the state of Selangor - Amirul Faiz Osman (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
Considering the importance of cash waqf in developing waqf instrument and enhancing the social economy of the ummah, the literature that contributes to understanding the factors that underlie a Muslim donors' decision to donate cash waqf has been extremely limited. This study aimed to empirically determine the significant determinants of cash waqf giving behavior (actual behavior and intention) and examine the mediating effect of intention on the relationship between predictors and cash waqf giving behavior. It also aimed to investigate the applicability of the Theory of Planned Behavior (TPB) in explaining cash waqf giving behavior in Malaysia context. A survey was conducted on 360 Muslim donors working in government and private agencies/institutions located in Selangor Darul Ehsan. The Data was analyzed using Structural Equation Modeling (SEM). Out of 19 hypotheses of cash waqf giving behavior, eight had significant direct effects namely intention, attitude, subjective norm, perceived behavior control and trust to cash waqf giving behavior, whilst religiosity, trust and perceived behavior control to intention. On the same note, three hypotheses had indirect significant effects (trust, religiosity and perceived behavior control toward cash waqf giving behavior mediated by intention). The study found that intention fully mediated the relationship between religiosity and cash waqf giving behavior. It was also found to be a partial mediator of the relationship between trust and perceived behavior control to cash waqf giving behavior. This findings strengthens the assumption that the theory of planned behavior is appropriate for this study in cash waqf giving behavior environment. Whereby, the constructed model has shown a reasonable goodness-of-fit index. This study contributes to the development of mutawallis in term of fundraising strategies that are more effective. The identification of the psychological factors that determine cash waqf giving behavior highlights ways in which mutawallis can increase the donation level i.e cash waqf. The study also add to the stocks of literature expecially on Islamic marketing. Similar studies could be extended to other state in Malaysia which have introduced cash waqf at their respective councils. Furthermore, the use of qualitative method is also needed to find more predictors that influence cash waqf giving behavior. This may provide a meaningful research area for the future.